Assessment of Energy Barriers Between ZrCuAlNi Amorphous Metal and Atomic Layer Deposition Insulators Using Internal Photoemission Spectroscopy. Issue 3 (24th January 2018) - Jenkins, Melanie A.; Klarr, Tyler; Austin, Dustin Z.; Li, Wei; Nguyen, Nhan V.; Conley, John F.
Abstract : The energy barrier heights between an ultra‐smooth amorphous metal electrode, ZrCuAlNi, and several atomic layer deposited (ALD) insulators are measured using internal photoemission (IPE) spectroscopy. ZrCuAlNi–insulator barriers are characterized within metal–insulator–metal (MIM) stacks with Al top contacts and results are compared with the Al/insulator barrier heights. The measured barrier heights at the ZrCuAlNi interface are found to be 3.3, 3.2, 3.0, and 2.2 eV for SiO2, Al2 O3, HfO2, and ZrO2, respectively. This barrier height trend is consistent with the electron affinity of the respective oxides. However, barriers for SiO2 and Al2 O3 are smaller than that ideally expected based on the reported vacuum work function of ZrCuAlNi, indicating a smaller ZrCuAlNi effective work function in these device structures. The measured Al barrier height results confirm previous reports of a negative dipole at the Al–ALD insulator interface. Abstract : Amorphous metals show promise as ultra‐smooth bottom electrodes for metal–insulator–metal devices. Internal photoemission spectroscopy, an opto‐electrical measurement technique, is used to directly measure, in situ, the height of the interface energy barriers in metal–insulator–metal structures between ZrCuAlNi, an amorphous metal bottom electrode, and several technologically relevant insulators (SiO2, Al2 O3, HfO2, and ZrO2 ) deposited via atomic layer deposition.